Co może dać wykładni prawa poststrukturalizm? - Szymańska, Małgorzata (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2018)
The presented article concerns the discourse in the field of literature research, and especiallythe interpretation of law theory. The whole discussion was set in a postmodern breakthrough,which appeared in the form of poststructuralism. Regarding the absence of a conceptualtheory of the interpretation of law embedded on postmodern foundations, it seems reasonableto attempt its application to the field of jurisprudence the of literature studies’ achievements,which are behind the stage of crystallization of the postmodernist theory of interpretation. Inthis paper the most representative theories of post-structuralism were briefly described:deconstruction, intertextuality and the reader response criticism. Regarding that in someissues (for example text ontologies) literary and legal discourse are not translatable, thestructural description of interpretation methods and the role of the interpreter seem to beapplicable in jurisprudence
Keywords: wykładnia prawa; interpretacja; poststrukturalizm; postmodernizm; strukturalizm; autor; prawodawca; tekst; tekst prawny; neopragmatyzm; intertekstualność; dekonstrukcja; interpretator